Seed Priming: Technique, Applications and Future Prospects in Vegetable Crops - RAJINDER SINGH; VARINDA; LAVANYA VIJ; NAVJYOT KAUR (Seed Research, 2026)
Horticulturists all over the world are struggling to meet the market’s increasing demands for highyielding quality vegetable crops. Seed priming presents a sustainable strategy to improve crop’s physiological and field characteristics helping farmers and seed producers to ensure high crop productivity and minimise any additional input cost by ensuring optimum crop stand under normal as well as stress conditions. Current scientific trends suggest that priming may aid in the reversal of age and storage-induced seed deterioration. It aids in lowering the levels of reactive oxygen and reactive nitrogen species in seeds with better reserve mobilization, increased efficiency of antioxidant enzymes and DNA repair mechanisms. This review paper aims to summarise the latest trends in the seed priming works on the types, mechanism and efficacy of seed priming techniques in vegetable crops with a particular focus on its potential to recover aged seed via priming, along with highlighting the gaps in the current investigations that ought to be filled with future studies. The findings elucidate the great potential of priming as a technique to become a major part of integrative resource management and crop improvement programmes to address issues such as food security and crop productivity in the era of climate change.